INCIDENCE, CLINICAL PRESENTATION, AND RISK FACTORS OF ECTOPIC PREGNANCY: A CROSS-SECTIONAL STUDY IN SIALKOT DISTRICT, PAKISTAN - IQBAL , S; ASHRAF , S; HUSNAIN , G; MUNIR , S; IQBAL , A; BIBI , A; MURAD , MA (Biological and Clinical Sciences Research Journal, 2024)
Ectopic pregnancy is a significant cause of maternal morbidity and mortality, particularly in low-resource settings like Pakistan. Understanding its incidence, symptoms, and risk factors is essential to improve diagnosis and management. Objective: To evaluate the incidence, clinical presentations, and risk factors associated with ectopic pregnancies across six hospitals in Sialkot district, Pakistan. Methods: A descriptive cross-sectional study was conducted over two months (November–December 2021). Data were collected retrospectively from hospital records, including demographic details, clinical symptoms, and risk factors. Descriptive statistics were calculated to summarize findings, and incidence rates were determined for each hospital. Results: Among 17,666 pregnancies, 276 cases of ectopic pregnancies were identified, yielding an incidence rate of 1.56%. The highest incidence was observed at Sardar Begum Hospital (2.20%). Urinary symptoms (97.5%), breast tenderness (77.5%), and gastrointestinal symptoms (75.0%) were the most common clinical presentations. Pelvic inflammatory disease (87.5%) and previous miscarriage or abortion (72.5%) were the most prevalent risk factors. Conclusion: The study highlights significant challenges in the diagnosis and management of ectopic pregnancies in Pakistan. Variability in hospital-specific incidence rates suggests the need for standardized diagnostic protocols and resource allocation. Addressing risk factors and enhancing awareness through education and training can improve maternal health outcomes.